Mechanical Performance Analysis of Cast Al−Si Alloy Cylinder Head Using Small Specimens. Issue 5 (28th October 2021) - Ren, Peirong; Zhao, Chengzhang; Huang, Weiqing; Zuo, Zhengxing; Yan, Kangjie; Li, Dongwei; Zhou, Haitao
Abstract : The mechanical properties' variation of the cylinder head caused by heterogeneities of microfeatures is systematically investigated by metallography measurements, X‐ray computed tomography, tensile and fatigue tests using small specimens, and fracture surface analysis. The results show that the microstructure and defect characteristics of the cylinder head exhibit high spatial heterogeneity, and the local mechanical performance is closely related to the microfeatures. The tensile and hardness properties of the top plate and flame plate are optimum, followed by the connecting wall, and the walls between inlet/exhaust and water jacket exhibit the worst properties. The difference in yield stress and hardness at different positions is relatively small, which has a close correlation with secondary dendrite arm spacing (SDAS), whereas the difference in ultimate tensile stress and elongation is relatively large. The fatigue life of the walls between inlet/exhaust and water jacket is significantly lower than that of the other positions. The porosity and SDAS are the two key parameters determining the fatigue strength of the alloy, and the relationship between fatigue life and fracture surface porosity and SDAS is established, which can predict well the fatigue life within a feasible scatter band. Abstract : The tensile strength at the top plate and flame plate of the cylinder head are optimum, followed by the connecting wall, and the walls between inlet/exhaust and water jacket exhibit the worst properties. The porosity and SDAS are the two key parameters determining the fatigue strength. The established relationship can predict well the fatigue life within a feasible scatter band.